2014
DOI: 10.1152/ajpgi.00128.2013
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic insulin receptor activity following injury

Abstract: Jiang S, Gavrikova TA, Messina JL. Regulation of hepatic insulin receptor activity following injury. Am J Physiol Gastrointest Liver Physiol 306: G886 -G892, 2014. First published April 3, 2014 doi:10.1152/ajpgi.00128.2013.-Impaired insulin receptor (IR) activity has been found in various models of insulin resistance, including models of injury or critical illness and Type 2 diabetes. However, mechanisms that modulate IR function remain unclear. With an animal model of critical-illness diabetes, we found insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It has been shown that hemorrhages result in metabolic disorders and insulin resistance, which contribute to the sequala of symptoms that result following a hemorrhage. The suppression of insulin resistance has demonstrated a protective effect against hemorrhage [ 14 , 15 ]. Our study revealed that mice, when exposed to hemorrhage, experienced glucose intolerance along with hyperinsulinemia, but the administration of irisin improved and attenuated the glucose intolerance induced by the hemorrhage and magnitude of hyperinsulinemia, indicating that irisin can ameliorate insulin sensitivity following a hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that hemorrhages result in metabolic disorders and insulin resistance, which contribute to the sequala of symptoms that result following a hemorrhage. The suppression of insulin resistance has demonstrated a protective effect against hemorrhage [ 14 , 15 ]. Our study revealed that mice, when exposed to hemorrhage, experienced glucose intolerance along with hyperinsulinemia, but the administration of irisin improved and attenuated the glucose intolerance induced by the hemorrhage and magnitude of hyperinsulinemia, indicating that irisin can ameliorate insulin sensitivity following a hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that mice, when exposed to hemorrhage, experienced glucose intolerance along with hyperinsulinemia, but the administration of irisin improved and attenuated the glucose intolerance induced by the hemorrhage and magnitude of hyperinsulinemia, indicating that irisin can ameliorate insulin sensitivity following a hemorrhage. Our previous studies, and others, have demonstrated that irisin-attenuated metabolic disorders, improved insulin sensitivity, and activated insulin signaling pathways contribute to the beneficial effects of irisin [ 15 , 16 , 17 ]. Although the precise molecular mechanism by which irisin mediates insulin sensitivity in hemorrhages is currently unknown, the improved insulin sensitivity by irisin plays a key role in protecting against hemorrhage.…”
Section: Discussionmentioning
confidence: 99%